2013
DOI: 10.1021/jp407252y
|View full text |Cite
|
Sign up to set email alerts
|

ESIPT and Photodissociation of 3-Hydroxychromone in Solution: Photoinduced Processes Studied by Static and Time-Resolved UV/Vis, Fluorescence, and IR Spectroscopy

Abstract: The spectral properties of fluorescence sensors such as 3-hydroxychromone (3-HC) and its derivatives are sensitive to interaction with the surrounding medium as well as to substitution. 3-HC is a prototype system for other derivatives because it is the basic unit of all flavonoides undergoing ESIPT and is not perturbed by a substituent. In this study, the elementary processes and intermediate states in the photocycle of 3-HC as well as its anion were identified and characterized by the use of static and femtos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…Depending on the solvent, fluorescence spectra comprise contributions from both S 1 A and S 1 B , giving rise to “dual” fluorescence 19 . Since ESIPT is ultrafast, emission yields from the excited reactant state however may be very low (see, e.g., in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the solvent, fluorescence spectra comprise contributions from both S 1 A and S 1 B , giving rise to “dual” fluorescence 19 . Since ESIPT is ultrafast, emission yields from the excited reactant state however may be very low (see, e.g., in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available 7-amino-4-methylcoumarin (AMC) is commonly used in various biological studies, and in particular AMC was used to develop a fluorescent turn-on enzymatic assays to study a large range of proteins including histone deacetylase (HDAC) [ 11 ], sirtuin (SIRT) [ 12 ], amidase [ 13 ], transglycosylase [ 10 ], and alkaline phosphatase (ALP) [ 14 ]. 7-Hydroxyisoflavones and 3-hydroxyflavones also exhibit fluorescence in biological buffers [ 15 , 16 ]. In our previous studies, we reported the development of 3-alkyl-6-methoxy-7-hydroxychromones (AMHC) as a fluorogenic scaffold for biological studies, which displays comparable fluorescent properties to AMC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus a substituent on the chromone unit as the phenyl group in 3-HF might even promote a faster ESPT since it hinders specific solute-solvent interactions enabling the pathway via the stabilised trans structure. 50,51 Further theoretical investigations on the structure and reactivity of 3-HC are presented in ref. 32 and 52-54. In order to achieve more information on the structure and reactivity of isolated 3-HC and defined aggregates with water we present in this paper the first molecular beam investigations of 3-HC including mass selected IR spectroscopy for the electronic ground state (IR/R2PI method) and the electronically excited state (UV/IR/UV method).…”
Section: Introductionmentioning
confidence: 99%